Anti-genotoxic effect of aqueous extracts of sun mushroom (Agaricus blazei Murill lineage 99/26) in mammalian cells in vitro - Martins de Oliveira, J.; Jordão, B. Q.; Ribeiro, Lúcia Regina [UNESP]; Ferreira Da Eira, A. [UNESP]; Mantovani, M. S. (Elsevier, 2002)
The sun mushroom is the popular name for the Agaricus blazei Murill fungus, a mushroom native to south-eastern Brazil, which has been frequently used in popular medicine mainly in the form of tea to treat various ailments (stress, diabetes, etc.). In the present study, the genotoxic and/or anti-genotoxic effects ofA. blazei on mammalian cells in culture was assessed by checking the increase or reduction of micronucleus (MN) frequency and comets. The sun mushroom (lineage 99/26) was used as aqueous extracts prepared (2.5%) at three different temperatures (60, 25 and 4°C). The in vitro micronucleus (MN) test in binucleated cells and comet assay were used in V79 cells cultivated in HAM-F10+DMEM medium (1:1), supplemented with 10% of fetal bovine serum. The experiments were divided into four treatment types: 1. Negative control; 2. Positive control with MMS; 3. Treatments with the three forms of extracts (60, 25 and 4°C); and 4. Treatments with the extracts in different associations (simultaneous, pre-treatment, post-treatment and simultaneous after pre-incubation for 1 h) with MMS. None of the A. blazei extracts show genotoxic activity. In the comet assay no protecting effect was found. The results obtained in the MN test showed that the three forms of extracts used had protective activity, suggesting that the compound or active ingredients of A. blazei are always present in these extracts. The greater protective efficiency of the simultaneous treatment and simultaneous treatment with pre-incubation mixture with MMS suggests that the extracts have an antimutagenic action of the desmutagenic type. © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Agaricus blazei; Anti-genotoxicity; Cell culture; Comet test; Methyl methanesulfonate; Micronucleus test; Agaricus blazei extract; antimutagenic agent; plant extract; unclassified drug; Brazil; cell culture; cell strain V 79; comet assay; drug effect; drug isolation; genotoxicity; in vitro study; incubation time; mammal; micronucleus; reduction; Agaricus; Animals; Antimutagenic Agents; Comet Assay; Cricetinae; Culture Media; DNA Damage; Micronucleus Tests; Mutagens; Temperature; Tumor Cells, Cultured; Basidiomycota; Bovinae; Fungi; Mammalia